A Numerical Study of Lewis Factor for Fin-and-tube Heat Exchangers under Dehumidifying Conditions - Han Weizhe; Ding Guoliang; Hu Haitao; Zhuang Dawei (Zhileng xuebao)
Lewis factor is an important parameter for heat and mass transfer process at dehumidifying conditions. A numerical model for calculating the Lewis factor and a correlation for engineering calculation are established. The Lewis factor is obtained through the numerical model of heat and mass transfer of air-side including the mass transfer between phases and the latent heat transfer using CFD. The effects of fin-and-tube heat exchanger geometries and working conditions as well as the feasibility of existing heat and mass transfer analogies are analyzed. Also the Lewis factor correlation is established through the numerical results. The heat and mass transfer deviations between numerical model and experimental data are 6.93% and 12.1% respectively. The correlation has relative deviation of 5.52% compared with numerical model. The results show that the obtained correlation has sufficient accuracy and applicability instead of numerical model.